2018
DOI: 10.1111/1759-7714.12888
|View full text |Cite
|
Sign up to set email alerts
|

Primary mediastinal dedifferentiated liposarcoma: Five case reports and a review

Abstract: BackgroundLiposarcoma has been subclassified histologically into well‐differentiated, myxoid, pleomorphic, and dedifferentiated types. The dedifferentiated type generally shows poorer prognosis than the well‐differentiated type. Because of its rarity, the clinicopathological features and clinical outcomes of primary mediastinal dedifferentiated liposarcoma remain unclear.MethodsFive patients with primary mediastinal dedifferentiated liposarcoma were treated at Shinshu University Hospital between January 2012 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 11 publications
(35 reference statements)
0
33
0
4
Order By: Relevance
“…A retrospective review from 1950-2018 of primary mediastinal dedifferentiated liposarcoma found 39 cases, of which 34 were treated with surgical resection, 2 with chemotherapy, and 3 unknown [11]. Another review from 2002-2016 found 19 cases of mediastinal dedifferentiated liposarcoma, of which 17 were treated with surgical resection, 1 with chemotherapy, and 1 unknown [12]. In these studies, only 1 patient treated without surgical resection had documented outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective review from 1950-2018 of primary mediastinal dedifferentiated liposarcoma found 39 cases, of which 34 were treated with surgical resection, 2 with chemotherapy, and 3 unknown [11]. Another review from 2002-2016 found 19 cases of mediastinal dedifferentiated liposarcoma, of which 17 were treated with surgical resection, 1 with chemotherapy, and 1 unknown [12]. In these studies, only 1 patient treated without surgical resection had documented outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This patient underwent chemotherapy with doxorubicin due to advanced inoperable disease and died less than 1 month after diagnosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of CDK4 leads to overexpression of CDK4 that can then bind to cyclin D at increased levels, leading to interference with the E2F-RB interaction that acts as a cell cycle progression check from the G1 to S phase transition ( 72 ). Few series exist examining mediastinal liposarcomas; however, the predominant tumor subtypes across all series appear to be well- and dedifferentiated liposarcoma, the majority of which showed the characteristic amplifications or IHC expression ( 73 - 76 ). Amplification of MDM2 and CDK4 has been shown to correlate extremely well with IHC for MDM2 and CDK4, allowing IHC to serve as an excellent screening tool, however confirmation of the diagnosis by molecular techniques is always recommended ( 77 ).…”
Section: Common Mediastinal Sarcomasmentioning
confidence: 99%
“…On CT, mediastinal liposarcoma manifests as a fat-containing, potentially infiltrative mediastinal mass with large or dominant areas of soft tissue nodularity or septations [2,8]. There are differing reports as to the most common mediastinal compartment including both the paravertebral (posterior) and prevascular (anterior) mediastinum [7,9]. The appearance on MRI is similar with a portion of the mass exhibiting the typical intensity characteristics of macroscopic fat: intrinsic T1 hyperintense signal with loss of signal on fat saturation sequences and other portions exhibiting soft tissue intensity characteristics [10].…”
Section: Imaging Appearancementioning
confidence: 99%
“…The recurrence rate is approximately 30% and is more common in those with positive margins on surgical resection [1]. Miura et al described local tumor recurrence as recurrent mediastinal soft tissue in three out of five cases of dedifferentiated liposarcomas on an average of 35 months' time despite initial complete surgical resection [9]. Radiation therapy following recurrence of mediastinal liposarcoma has been effective in a few cases, however, the effectiveness of radiation or chemotherapy is unknown given the limited number mediastinal liposarcoma cases [9,16].…”
Section: Treatment and Prognosismentioning
confidence: 99%